Highly Conductive Cellulose Network/Polyaniline Composites Prepared by Wood Fractionation and In Situ Polymerization of Aniline. Issue 7 (12th July 2019) - Ke, Shaoqiu; Ouyang, Tulong; Zhang, Kai; Nong, Yuhong; Mo, Ying; Mo, Qiufeng; Wei, Yongxuan; Cheng, Fangchao
Abstract : Front Cover : In article number 1900112 by Fangchao Cheng and co‐workers, cellulose network/polyaniline composites with hierarchical porous nanostructure of wood are successfully prepared, which exhibit high conductivity and promising specific capacitance when used as electrode materials in all‐solid‐state supercapacitors.